Tanggung Jawab Guru Pendidikan Agama Kristen Dalam Melaksanakan Profesinya Sebagai Pendidik - Heri Kiswanto; Syahur, Heri (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2022)
Teaching is a unique profession because there are so many competencies that must be possessed in carrying out its duties to prepare future generations. The ideal teacher, not just a teacher who meets technical requirements: such as smart, clever, or an expert in the field of science they have; but more importantly, the teacher must be able to position himself as an agent of change. For this reason, Christian Religious Education Teachers must have roles and responsibilities personally, socially, intellectually, morally and spiritually. First, independent personal responsibility, namely being able to understand himself, manage himself, control himself and respect and develop himself. Second, social responsibility is realized through the competence of teachers from the social environment and having effective interactive abilities. Third, intellectual (professional) responsibility is realized through the mastery of various sets of knowledge and skills needed to support their duties. Fourth, spiritual and moral responsibility is realized through the appearance of teachers as religious beings whose behavior does not always deviate from religious and moral norms. This article provides an understanding of the responsibilities of Christian Religious Education teachers that must be carried out in carrying out their duties. With the aim that what is done by a Christian Religious Education Teacher can be accounted for before God and within the educational institution itself. This article uses descriptive qualitative research with a literature and biblical text approach and focuses on the discussion of the Teacher's Responsibilities to his Profession Keywords: responsibility; teacher; christian education. Guru adalah merupakan profesi yang unik karena begitu banyaknya kompetensi yang harus dimiliki dalam melaksanakan tugasnya mempersiapkan generasi yang akan datang. Guru yang ideal, bukan sekedar guru yang memenuhi syarat-syarat teknik: seperti pintar, pandai, atau pakar di bidang ilmu yang dimiliki; melainkan yang jauh lebih penting dari itu semua, guru harus mampu menempatkan dirinya sebagai agen perubahan “agent of change.” Untuk itu Guru Pendidikan Agama Kristen harus memiliki peran dan tanggung jawab secara pribadi, sosial, intelektual, moral dan spiritual. Pertama, tanggung jawab pribadi yang mandiri yaitu mampu memahami dirinya, mengelola dirinya, menngendalikan dirinya dan menghargai serta mengembangkan dirinya. Kedua, tanggung jawab sosial diwujudkan melalui kompetensi guru dari lingkungan sosial serta memiliki kemampuan interaktif yang efektif. Ketiga, tanggung jawab intelektual (profesional) diwujudkan melalui penguasaan berbagai perangkat pengetahuan dan keterampilan yang diperlukan untuk penunjang tugasnya. Keempat, tanggung jawab spiritual dan moral diwujudkan melalui penampilan guru sebagai makhluk beragama yang perilakunya senantiasa tidak menyimpang dari norma agama dan moral. Artikel ini memberikan pemahaman terkait tanggung jawab-tanggung jawab guru Pendidikan Agama Kristen yang harus dikerjakan dalam menjalankan tugasnya. Dengan tujuan agar apa yang dikerjakan oleh sorang Guru Pendidikan Agama Kristen bisa dipertanggung jawabkan dihadapan Tuhan dan didalam lembaga pendidikan itu sendiri. Artikel ini mengunakan penelitian kualitatif deskriptif dengan pendekatan pustaka dan teks Alkitab dan berfokus pada pembahasan tentang Tanggung Jawab Guru Terhadap Profesinya.